The value of the middleman in the supply chain of South African tyre production - Cornelius, André G (Rhodes University, Faculty of Commerce, Investec Business School, 2008)
Only a few middlemen linking chemical intermediate product supply to world tyre productions have managed to survive new direct business models. In fact, the only region, where the practice of using a middleman in the supply chain of tyre production, for a certain primary manufacturer, is in South Africa. Tyre producers in other world regions, similar in market complexity to South Africa, have experienced the elimination of the middleman. Hence the question of this research, why is the middleman in the supply chain of tyre production in South Africa still a better option than that of direct business models? To begin with, the thesis stated that the middleman in the supply chain of South African tyre producers delivers better value than that of the direct business model. To prove/disprove this thesis, the principle that value is a trade-off between what you get for what you give was the basis of this research (Zeithaml, 1998). Further, a model was developed, from secondary literature, to conceptualise this trade-off to provide evidence to prove/disprove that the middleman provides greater value than value from the direct business model. From this point, the research approach was to collect data through interviews to find out the most important aspect of value created by the middleman. Data collected were analysed, using the structure of the model as a guide, to find evidence of the trade-off. This analysis provided evidence that the relationship between the middleman and the tyre producers in South Africa and between the middleman and primary product supplier is the value that the direct business model cannot replace.
Keywords: Tires -- Industrialists -- South Africa; Tire Industry -- South Africa; Commercial agents -- South Africa; Business logistics -- Management -- South Africa; Physical distribution of goods -- Management; Commercial agents -- South Africa; Marketing channels -- Management -- South Africa